Skirining fitokimia ekstrak etanol kulit buah sirsak (Annona muricata Linn) dan uji aktivitas antioksidan dengan metode DPPH - Nur Alim; Nurul Jummah; Agus Sangka Pratama; Nurdiyanti Nurdiyanti (Sasambo Journal of Pharmacy, 2021)
Phytochemical screening research on the ethanol extract of soursop (Annona muricata Linn) peel and antioxidant activity was tested using the DPPH method. The purpose of this study was to determine several classes of compounds found in soursop rind and to determine the antioxidant activity of ethanol extract of soursop rind against DPPH free radicals. The results showed ethanol extract of positive soursop fruit skin containing flavonoids, tannins, and terpenoids. of soursop fruit skin extract was carried out by DPPH method results obtained IC50 value of 192.13 µg / mL ± 5.198137 which was categorized as weak.